Asuhan keperawatan pada lansia diabetes melitus dengan ketidakstabilan kadar glukosa darah di Kecamatan Cibiru Kota Bandung - Darajat, Agus Miraj; Muslim, Dede Nur Aziz; Indarna, Asep Aep; Pratidina, Eki; Rizqi, Soni Mochamad (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2024)
Background: Diabetes Mellitus (DM) is a metabolic disease characterized by hyperglycemia which occurs because the pancreas is unable to secrete insulin, insulin action is disrupted, or both. There has been an increase in the global prevalence of DM of around 8.3% in the 20-79 year age group and it is estimated that there are 2.2 million deaths with the percentage due to DM occurring before the age of 70 years, especially in developed countries. country. with low and middle economic status. Purpose: To compile the results of nursing care and identify the benefits of DM exercise in stabilizing the effectiveness of unstable sugar levels in nursing care for elderly DM. Method: Descriptive research with a case study approach on 2 elderly people suffering from diabetes mellitus (DM). This research was conducted in Cibiru District, Bandung City, using a nursing care format for the elderly. Examination data was collected using the Bartel Index and Katz Index on the elderly body. Researchers carry out inspection, palpation, auscultation and percussion on clients. Results: After being given 3J DM diet education, namely type, amount and hours as well as teaching DM exercises, sugar levels decreased, the feeling of tingling decreased, and they were able to do DM exercises. Conclusion: DM exercise is useful in controlling unstable glucose levels in elderly DM nursing care. Suggestion: There is a need for further examination and monitoring of elderly people who experience physical changes in DM sufferers so that their physical health is maintained. Community health centers can carry out intensive visit programs specifically for elderly people who require total dependency. Further research is needed by adding family support variables and actors that worsen elderly illnesses. Keywords: Blood Glucose Instability; Diabetes Mellitus; Glucose Levels. Pendahuluan: Diabetes Melitus (DM) adalah suatu penyakit metabolik yang ditandai dengan adanya hiperglikemia yang terjadi karena pankreas tidak mampu mensekresi insulin, gangguan kerja insulin,ataupun keduanya. Terjadi peningkatan prevalensi global DM sekitar 8.3% pada kelompok usia 20-79 tahun dan diperkirakan terdapat 2.2 juta kematian dengan persentase akibat penyakit DM yang terjadi sebelum usia 70 tahun, khususnya di negara-negara dengan status ekonomi rendah dan menengah. Tujuan: Untuk menyusun hasil asuhan keperawatan dan mengidentifikasi manfaat senam DM dalam menstabilkan efektifitas ketidakstabilan kadar gula pada asuhan keperawatan lansia penderita DM. Metode: Penelitian deskriptif dengan pendekatan studi kasus kepada 2 lansia yang mengalami diabetes melitus (DM). Penelitian ini dilakukan di Kecamatan Cibiru Kota Bandung menggunakan format asuhan keperawatan pada lansia. Pengumpulan data pemeriksaan dengan cara Bartel Index dan Katz Indeks pada tubuh lansia. Peneliti melakukan tindakan inspeksi, palpasi, auskultasi, dan perkusi yang dilakukan pada klien. Hasil: Setelah dilakukan edukasi diit DM 3J yaitu, jenis, jumlah, dan jam serta mengajarkan senam DM, kadar gula mengalami penurunan, kesemutan berkurang, dan mampu melakukan senam DM. Simpulan: Senam DM bermanfaat dalam mengontrol ketidakstabilan kadar glukosa pada asuhan keperawatan lansia dengan DM. Saran: Perlu adanya pemeriksaan dan pemantauan lebih lanjut pada lansia yang mengalami perubahan fisik dengan DM agar terjaga kesehatan jasmaninya. Pihak puskesmas dapat melakukan program khusus kunjungan intensif pada lansia yang membutuhkan ketergantungan total. Penelitian selanjutnya dibutuhkan dengan menambahkan variabel dukungan keluarga dan aktor yang memperberat penyakit lansia. Kata Kunci: Diabetes Melitus; Kadar Glukosa; Ketidakstabilan Glukosa Darah.